Analisis Mendalam tentang Kesenjangan Gender di Indonesia: Perspektif Teori dan Kebijakan - Ega Anjellika; Dwi Putri Lestarika (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The gender gap in Indonesia remains a significant issue even though various policies have been implemented to reduce it. This article analyzes the inequality between men and women in the social, economic, educational, and political fields, and explores relevant social theories, such as Structural Functionalism, Feminism, and Institutional Economics. Based on data from the Central Statistics Agency (BPS) and other reports, the gender gap in Indonesia is still seen in low female labor force participation, inequality in access to education, and income disparities. Policies such as Law No. 13 of 2003 on Manpower and Gender Mainstreaming (PUG) have been enacted, but challenges in patriarchal culture and economic limitations still hamper efforts to achieve equality. This article recommends strengthening gender equality education, policy oversight, and inclusive economic development as strategic steps to reduce the gender gap in Indonesia.